Construction of a stable lithium sulfide membrane to greatly confine polysulfides for high performance lithium–sulfur batteries. Issue 18 (25th April 2018) - Wu, Chao; Guo, Chunxian; Wu, JingGao; Ai, Wei; Yu, Ting; Li, Chang Ming
Abstract : A stable lithium sulfide membrane is constructed in situ to wrap the mixed sulfur/C material surface of a lithium–sulfur battery (LSB) by delicately tuning the galvanostatic discharge current. Abstract : A stable lithium sulfide membrane is constructed in situ to wrap the mixed sulfur/C material surface of a lithium–sulfur battery (LSB) by delicately tuning the galvanostatic discharge current. The membrane offers unique and selective channels which allow only ions/small sulfides to pass through and confine polysulfide transport, restricting the shuttle effect, and thus providing a large capacity of 685 mA h g −1 at 1C and a long-lasting cycling stability (0.03% capacity decay per cycle). This LSB, which is much superior to the same sulfur-loaded battery without the membrane (0.26% capacity decay per cycle over 207 cycles and 213 mA h g −1 at 1C), is the best among all reported plain carbonaceous host material-based LSBs. The mechanism responsible for such dramatically improved performance is discussed in detail. This work not only offers a facile approach to greatly improve the capacity and stability of LSBs for practical applications but also offers new scientific insights into LSB design.